Innate inflammatory markers for predicting survival in retroperitoneal sarcoma. Issue 8 (17th August 2020) - Netanyahu, Yael; Gerstenhaber, Fabian; Shamai, Sivan; Sher, Osnat; Merimsky, Ofer; Klausner, Joseph M.; Lahat, Guy; Nizri, Eran
Abstract: Introduction: Existing prognostic tools for retroperitoneal sarcomas (RPS) utilize parameters that can be accurately determined only postoperatively. This study evaluated the application of the neutrophil‐to‐lymphocyte ratio (NLR) and C‐reactive protein (CRP) levels for predicting prognosis in primary RPS. Materials and Methods: We retrospectively analyzed our database of patients with primary RPS operated between 2008 and 2018. The NLR was calculated from preoperative blood tests and its association with outcomes was determined. Results: The NLR values of 78 suitable patients were analyzed. Patients were classified in the NLR‐high group if the NLR was ≥2.1. High‐grade tumors were more common in the NLR‐high group (71.6% vs 48%, P = .02). NLR‐high patients had impaired overall survival (OS) and progression‐free survival (PFS) compared to NLR‐low patients (median OS not reached vs 74 months 95% confidence interval [CI]: 21.6‐126.4, P = .03; median PFS not reached vs 48 months 95% CI: 6.5‐98.6, P = .06, respectively). Multivariate analysis showed statistical significance only for PFS but not for OS (hazard ratio [HR] = 4.1, P = .03; HR = 2.3, P = .3). Patients with low CRP levels had improved OS and PFS. Conclusions: The NLR may serve as a preoperative, easily derived marker for prognosis in RPS. Serum biomarkers may prove useful in these large and spatially heterogeneous tumors.